Италмас: легенда / Михаил Петров ; [перевод с удмуртского В. Семакина ; художник Э. Морозов] - Петров Михаил Петрович (Удмуртия, 1984)
Экземпляры: ф.1 (ретро) / Инвентарный номер: 9030 / Сис.шифр: 84(2Рос=Удм)6 / Авт.знак: П 30 / ГРНТИ: 17.82.90 / ББК: 84(2Рос=Удм)6